Methyl Chloride Measurements in the Taylor Dome M3C1 Ice Core - Aydin, Murat; Saltzman, Eric (IEDA: US Antarctic Program Data Center, 2014)
This data set includes methyl chloride (CH3CI) measurements made on air extracted from 62 samples from the Taylor Dome M3C1 ice core in East Antarctica. CH3CI was measured in air from the Taylor Dome ice core to reconstruct an atmospheric record for the Holocene (11-0 kyr B.P.) and part of the last glacial period (50-30 kyr B.P.).